The Reinforcement of Pesantren as Harmonization Agent of Religious Life in Pesantren “AL-FATAH” Singkawang, West Kalimantan - Muhtifah, Lailial (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This article is to explore the reinforcement of Pesantren as harmonization agent of religious life, the foundation, strategies, procedures, and the assessment process of harmonization in pesantren